2022
DOI: 10.3390/nano12234130
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic Behavior of Polypropylene Nanocomposites Filled with Graphene Functionalized by Alkylated Chains

Abstract: Owing to stringent international environmental and fuel efficiency requirements for lightweight automotive systems, polymer composites have attracted widespread attention. Polypropylene (PP) is a widely employed commercial polymer because of its lightweight and low cost. In this study, PP nanocomposites were fabricated to reduce the moisture absorption of PP composites in automotive headlamp housings. Alkylated chemically modified graphene (CMG-R) was synthesized to reduce the surface hydrophilicity of graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The surface of MMT-Ca 2+ is hydrophilic because of its structure (as discussed earlier), and as illustrated in Figure 6, owing to the hydrophilic properties of MMT-Ca 2+ , a substantially low contact angle (12.0 • ) was obtained. As previously reported by our research group [17], the surface of GO is hydrophilic because of the hydroxyl and carboxyl groups and exhibits a low water contact angle (53.5 • ). However, CMG + is hydrophobic, which can be attributed to the reduction in the number of hydrophilic functional groups (hydroxyl and carboxyl groups) and the increase in the crystallinity of graphene.…”
Section: Nanofiller Characterizationsupporting
confidence: 73%
See 3 more Smart Citations
“…The surface of MMT-Ca 2+ is hydrophilic because of its structure (as discussed earlier), and as illustrated in Figure 6, owing to the hydrophilic properties of MMT-Ca 2+ , a substantially low contact angle (12.0 • ) was obtained. As previously reported by our research group [17], the surface of GO is hydrophilic because of the hydroxyl and carboxyl groups and exhibits a low water contact angle (53.5 • ). However, CMG + is hydrophobic, which can be attributed to the reduction in the number of hydrophilic functional groups (hydroxyl and carboxyl groups) and the increase in the crystallinity of graphene.…”
Section: Nanofiller Characterizationsupporting
confidence: 73%
“…In contrast, for polymers with low moisture-absorbing ability, such as PP, the hydrophilic properties of the clay filler are expected to have a significant impact. In our previous study [17], we demonstrated the hygroscopic behavior of PP nanocomposites prepared with alkylated graphene. However, the mechanical properties of the chemically modified PP/alkylated graphene nanocomposites were poor and, therefore, require improvement.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations